Engaging the Transgender Community to Improve Medical Education and Prioritize Healthcare Initiatives. Issue 2 (3rd April 2018) - Noonan, Emily J.; Sawning, Susan; Combs, Ryan; Weingartner, Laura A.; Martin, Leslee J.; Jones, V. Faye; Holthouser, Amy
ABSTRACT: Phenomenon : Transgender patients experience discrimination, limited access to care, and inadequate provider knowledge in healthcare settings. Medical education to address transgender-specific disparities is lacking. Research that engages transgender community members may help address health disparities by empowering patients, increasing trust, and informing medical curricula to increase competence. Approach : A 2015 Community Forum on Transgender Health Care was hosted at the University of Louisville School of Medicine, which included healthcare professionals and transgender community members to facilitate dialogue among mixed-participant groups using a World Café model. Fifty-nine participants discussed the status of transgender healthcare and made recommendations for local improvements. A follow-up survey was administered to 100 individuals, including forum participants and their referrals. The forum discussion and survey responses were analyzed to determine common perceptions of transgender healthcare, priorities for improvement interventions, and themes to inform curriculum. Findings : The community forum discussion showed that local transgender care is overwhelmingly underdeveloped and unresponsive to the needs of the transgender community. The follow-up survey revealed that priorities to improve transgender care included a multidisciplinary clinic for lesbian, gay, bisexual, and transgender (LGBT) patients, an LGBT-friendly network of physicians, and more training for providers and support staff. This mutually constructive engagement experience influenced reform in undergraduate curricula and continuing education opportunities. Insights : Community engagement in healthcare disparities research can cultivate improbable discussions, yield innovative insight from marginalized populations, and build relationships with community members for future collaborations and interventions. Societal acceptance of transgender identities, which could be promoted through healthcare providers, could stimulate significant progress in transgender healthcare. Supplemental educational interventions for practicing physicians will improve the current conditions of transgender healthcare, but a comprehensive medical school curriculum specifically for transgender health that includes interactions between the transgender community and medical students could be particularly impactful.